Overview of Edge Computing With Software Defined Networks - Devi, B. Parvathi; Vallinayagi, V (International Journal of Computer Sciences and Engineering, 2025)
loud Computing is a technology, which involves sharing the resources of both hardware and software to the customers through the Internet with the reduced cost and time. But still it has many security and time related issues. To overcome the difficulties faced by the cloud many new technologies are found. In that the new technology named Edge computing most over satisfy the customers need with secured manner and within the time constraint given by the customer. In Edge the data are not accessed in the main server of the cloud instead they process it in the nearby data centres, so the time saved and security is also maintain only in the prescribed range resources. This paper includes the architecture and functions of the Edge computing, which gives new ideas to the researchers in the Edge filed